2014
DOI: 10.1021/es5017922
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated Biphenyls in Glaciers. 1. Deposition History from an Alpine Ice Core

Abstract: We present a highly time-resolved historical record of polychlorinated biphenyls (PCBs) from an Alpine ice core (Fiescherhorn glacier, Switzerland). Introduced in the 1940s, PCBs were widely used industrial chemicals. Because of their persistence they are still found in the environment, long after their production phase-out. The Fiescherhorn ice core record covers the entire time period of industrial use of PCBs, that is, 1940-2002. The total concentration of six PCBs varies from 0.5 to 5 ng L(-1) and reveals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 38 publications
3
48
0
Order By: Relevance
“…The global usage of PCBs culminated in the mid 1970's (Breivik et al, 2007), and since then concentrations in the environment have decreased dramatically (Schuster et al, 2010;Airaksinen et al, 2014;Pavlova et al, 2014;Rasmussen et al, 2014). Currently, the PCB decline in the environment is levelling off (Hansson et al, 2006;Thevenon et al, 2013;Airaksinen et al, 2014), which for the Baltic Sea also would imply stabilising PCB concentrations in biota.…”
Section: Introductionmentioning
confidence: 99%
“…The global usage of PCBs culminated in the mid 1970's (Breivik et al, 2007), and since then concentrations in the environment have decreased dramatically (Schuster et al, 2010;Airaksinen et al, 2014;Pavlova et al, 2014;Rasmussen et al, 2014). Currently, the PCB decline in the environment is levelling off (Hansson et al, 2006;Thevenon et al, 2013;Airaksinen et al, 2014), which for the Baltic Sea also would imply stabilising PCB concentrations in biota.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] The highest OCP concentrations measured englacially, to date, were found in ice cores from the Italian Alps in 2001 (20 ng/L), [5] containing chemicals α-and ϒ-HCH. While subsequent OCP studies in the Swiss Alps found concentrations of the same magnitude (PCB-12.5 ng/L), [6] all studies from the Arctic, including Svalbard (PCB-1.5 ng/L) [7] and Canada (DDT-2.5 ng/L) [9,10] have found lower OCP concentrations. The atmospheric range potential of each chemical is determined in part by distance from source, air mass transport, weight and volatility, with some pesticides able to redeposit multiple times.…”
Section: Introductionmentioning
confidence: 92%
“…Particle sorbtion within Jarvis' sediment-rich ice layers may increase OCP loss during englacial and supraglacial melt events. [52][53][54] Ice core concentrations indicate that ΣDDT is the greatest contributor to OCP concentrations within Jarvis Glacier. ΣDDT deposition may be a result of use prior to the Stockholm Convention ban, however, continuing DDT use in Asia to combat malaria may explain why comparatively elevated rates occur in samples proximal to the surface.…”
Section: Ice Core Ocp Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even almost thirty years after they were banned in China and other numerous countries [1], high concentrations of organochlorine compounds still exist in soil, sediment, water and air [2][3][4]. Their persistence, toxicity and bioaccumulation greatly affect the environmental qualities, and animal and human health [5].…”
Section: Introductionmentioning
confidence: 99%